Report Card on Minority and Female Participation in Construction Trade Apprentices in the Milwaukee Area: Who's in the Pipeline for Skilled Construction Trades - (:unkn) unknown (My University, 2006)
This report provides racial/ethnicity and gender data on apprentices in the construction trades in the Milwaukee metro area from 1999 to 2005. The data has been supplied by the Wisconsin Department of Workforce Development (DWD) Bureau of Apprenticeship Standards (BAS). The report analyzes these records to drill down to the level of individual employers and joint apprenticeship committees, where decisions are made related to employment of apprentices. Report cards are provided for 475 Milwaukee area companies with construction trade apprentices, 14 Milwaukee and Waukesha area joint apprenticeship committees (JACs), one statewide committee, and one non-union program.
Keywords: construction trades; apprenticeships; affirmative action; African Americans; Hispanics